2020
DOI: 10.1016/j.jri.2020.103213
|View full text |Cite
|
Sign up to set email alerts
|

The role of Interleukin-4 in COVID-19 associated male infertility – A hypothesis

Abstract: Highlights COVID-19 is associated with the comorbidities such as male reproductive dysfunction COVID-19 patients connected with the male reproductive dysfunction have decreased spermatogenesis, attenuated levels of testosterone via altering the cytokines such as TNF-α, IL-4, IL-6, and IL-12. Inflammation is one of the causes of COVID-19 linked to male reproductive dysfunction through TNF-α and interferon. IL-4 activated by the Th2 cells … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
34
0
3

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 96 publications
1
34
0
3
Order By: Relevance
“…Therefore, based on these studies, it can be explained, how an increase in expression of inflammatory cytokines, including TNF-α, IL-1β and IL-6, has caused a decrease in BTB proteins expression including occludin, claudin-11 and connexin-43 in the COVID-19 group. Another study has reported that the levels of pro-inflammatory chemokines and cytokines, including IL-6, TNF-α, and MCP-1, play a noteworthy role in the immunopathology of SARS-CoV-2, in semen samples of COVID-19 patients increased [ 30 ]. However, one of the mechanisms underlying COVID-19-associated barrier disruption is increasing the susceptibility of testicular cells to interactions with other immune cells, leading to increased infiltration across the barrier 31).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, based on these studies, it can be explained, how an increase in expression of inflammatory cytokines, including TNF-α, IL-1β and IL-6, has caused a decrease in BTB proteins expression including occludin, claudin-11 and connexin-43 in the COVID-19 group. Another study has reported that the levels of pro-inflammatory chemokines and cytokines, including IL-6, TNF-α, and MCP-1, play a noteworthy role in the immunopathology of SARS-CoV-2, in semen samples of COVID-19 patients increased [ 30 ]. However, one of the mechanisms underlying COVID-19-associated barrier disruption is increasing the susceptibility of testicular cells to interactions with other immune cells, leading to increased infiltration across the barrier 31).…”
Section: Discussionmentioning
confidence: 99%
“…Following this same line of thought, Renu et al demonstrated that while many carriers of the disease are asymptomatic, the deleterious reproductive effects in the infected man can be silent and, thus, make these conditions more serious due to a late diagnosis (Renu et al, 2020).…”
Section: Viral Infectionmentioning
confidence: 94%
“…The most serious cases of COVID-19 are accompanied by a high level of IL-6, with receptors expressed in testicular cells, which justifies male gonadal involvement and the appearance of orchitis as a complication of Sars-CoV-2 (Renu et al, 2020;Haghpanah et al, 2021).…”
Section: Physiopathologymentioning
confidence: 99%
“…In COVID-19, T helper type 2 cells activate the IL-4 (through IgG and IgE) and mediate the apoptosis which may cause male infertility. On the other hand, IL-4 decreases the level of the ACE-2 which leads to male infertility in COVID-19 [ 82 ]. High level of IL-6S is observed in severe cases of COVID-19 and its receptors are highly expressed in testicular cells [ 83 ].…”
Section: Testicular Immunitymentioning
confidence: 99%